On the mean monthly precipitation regime of selected regions of Sabah (East Malaysia) - Camerlengo, Alejandro L. (1999)
In this paper the monthly rainfall distribution on Sabah is addressed. Eight types of rainfall distribution may be distinguished. The importance of the two inter-monsoon periods in the monthly rainfall distribution as well as the two (seasonal) monsoon winds at both coasts of Sabah is well established. In this regard, our results confirm previous findings for Peninsular Malaysia.